Pemberian Air Susu Ibu dengan Status Gizi dan Kejadian Infeksi pada Bayi 6 - 8 Bulan di Desa Suradadi Kecamatan Suradadi Kabupaten Tegal - Setyorini, Djatiningsih; Sulistyowati, Enik; Supadi, Johanes (Poltekkes Kemenkes Semarang, 2013)
Background : Malnutrition is the most significant factor for infant mortality. Exclusive breastfeeding for infants contributed to the Nutritional Status and Infant Health. In Suradadi Health centre (Puskesmas), there were some problems, such as the prevalence of exclusive breast feeding under minimum standard of service and the high incidence of malnutrition, Respiratory Tract Infection and Diarrhoea.Objectives : To analyze breastfeeding relationship with the nutritional status and Incident of Infection in 6-8 months Infants.Method : This type of study was explanatory study with cross sectional approach. Subjects were all of 6-8 months infants in study area. Variables are exlusive breastfeeding, nutrition status and infection. The statistical test was applied by using Fisher's exact with test of closeness contingency coefficient.Results : There were 24.6% infant being exclusive breastfeeding. Some of them ( 94.7%) have well-nourished and wasting s were 1.8%. There were 84.2% had infection. There was no association between exclusive breastfeeding an nutritional status ( p=1.00), however there was an association between exclusive breastfeeding and infection incidence (r=0,605,p =0.00) .Conclusion : There was no relation between exclusive breastfeeding with Nutritional Status and there was a significant relation between the Exclusive Breastfeeding and Infection incidence with a strong level of closeness in 6-8months infants.